Controllable antimicrobial properties of silver ion-exchanged niobate and tantalate compounds - Withanage Isuru Udakara Withanage (Taylor & Francis Group, 2021)
We designed pyrochlore-type potassium niobate (KN) and potassium tantalate (KT) by introducing silver ions to improve their antibacterial efficiency. KN and KT samples were used as ion-exchangeable parent compounds, and molten AgNO3 was used for the ion-exchange reaction. The formation of silver ion-exchanged compounds with various molar ratios, which was investigated by X-ray diffraction (XRD), indicated a clear structural transformation of KN after complete ion-exchange. The antibacterial efficacy of these samples was investigated using the colony count method, and the relative antibacterial activity was compared based on the area of the inhibition zone. The results indicated that silver ion-exchanged samples with molar ratios of Ag/Nb = 0.05, 0.44, 0.67, and Ag/Ta = 0.07, 0.44 0.64 exhibited complete (100%) antibacterial activity against Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative). Among the silver ion-exchanged samples, KAN1 and KAT1 exhibited the highest antibacterial activities because of the controlled release of Ag+ ions through their tunnel structure. In this study, it was found that tunable silver-release properties of pyrochlore-type niobate and tantalate enable the optimization of discharged Ag+ ions, which inhibits the bacterial efficacy in different extents, thus suggesting their use in various biomedical applications.